2021
DOI: 10.1080/20008198.2020.1860356
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment disorder, traumatic stress, depression and anxiety in Poland during an early phase of the COVID-19 pandemic

Abstract: Background:The current COVID-19 pandemic is associated with a variety of stressors. Preliminary research has demonstrated that general public are experiencing a range of psychological problems, including stress-related disturbances. However, to date, there is not much research on the prevalence of adjustment disorder during the current pandemic. Objectives: This study aimed to assess the prevalence and severity of symptoms of adjustment disorder compared to posttraumatic symptoms, depression and generalized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 33 publications
(56 reference statements)
6
56
1
5
Order By: Relevance
“…Female gender was associated with higher AjD symptom levels. Two earlier studies found positive associations between female gender and selfreported symptoms of AjD during the initial phase of the COVID-19 pandemic (Dragan et al, 2021;Rossi et al, 2020). Additional studies reported relationships between female gender and psychological distress, anxiety, and depression during the pandemic (Liu et al, 2020;Mazza et al, 2020;Rossi et al, 2020).…”
Section: Risk and Protective Factorsmentioning
confidence: 95%
“…Female gender was associated with higher AjD symptom levels. Two earlier studies found positive associations between female gender and selfreported symptoms of AjD during the initial phase of the COVID-19 pandemic (Dragan et al, 2021;Rossi et al, 2020). Additional studies reported relationships between female gender and psychological distress, anxiety, and depression during the pandemic (Liu et al, 2020;Mazza et al, 2020;Rossi et al, 2020).…”
Section: Risk and Protective Factorsmentioning
confidence: 95%
“…Perceptions and attitudes toward negative and powerful life events can be related to the type of defense mechanisms an individual employs and the level of functioning of the ego ( 1 ). To many people a sudden shift in their everyday lives due to the recent COVID-19 pandemic and lock-down could have been a traumatizing event and may have triggered the use of maladaptive defense mechanisms ( 2 , 3 ). That could be especially true among individuals with weaker ego, who use more maladaptive defense mechanisms ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent reviews a variety of psychological problems have been identified across studies on COVID-19 pandemic-related mental health effects [1][2][3][4]. One of the most commonly reported mental health problems during the pandemic are disturbances in stress reactions, such as posttraumatic stress disorder (PTSD) symptoms and adjustment disorder (AD) [5][6][7]. For instance, a meta-analysis found a pooled prevalence of post-pandemic PTSD of 23% [8] and two studies from the UK and Poland reported AD prevalence rates during the COVID-19 pandemic of 16% and 49%, respectively [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly reported mental health problems during the pandemic are disturbances in stress reactions, such as posttraumatic stress disorder (PTSD) symptoms and adjustment disorder (AD) [57]. For instance, a meta-analysis found a pooled prevalence of post-pandemic PTSD of 23% [8] and two studies from the UK and Poland reported AD prevalence rates during the COVID-19 pandemic of 16% and 49%, respectively [5,6]. These rates are higher than one-year prevalence rates of 4-5% PTSD [9,10] and point prevalence rate of 1% of AD [11] found in the general population before the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation